AIDS impact special issue 2015: interpersonal factors associated with HIV partner disclosure among HIV-infected people in China. (24th March 2016) - Qiao, Shan; Li, Xiaoming; Zhou, Yuejiao; Shen, Zhiyong; Tang, Zhenzhu
ABSTRACT: HIV partner disclosure may facilitate social support, improve psychological well-being among HIV-infected individuals, and promote HIV testing and HIV prevention among their sexual partners. A growing literature emphasizes the critical role of interpersonal factors may play in decision-making and practice regarding HIV partner disclosure. However, there is a dearth of empirical studies that investigate how interpersonal factors may be associated with HIV partner disclosure. Using cross-sectional data collected from 791 HIV-infected people in Guangxi China, we examined the associations between these two interpersonal factors (quality of relationship with partner and family communication) and HIV partner disclosure. Descriptive analysis, t -test analysis, and gender stratified GLM analysis were conducted. We find that disclosing HIV status to partners was significantly related to better quality of relationship with partners and open and effective family communication. Gender and partner HIV status might moderate the associations between interpersonal factors and HIV partner disclosure. Our findings suggest the importance of considering relationship quality and enhancing open and comfortable family communication in HIV disclosure interventions. Gender difference and partner HIV status should be also considered in HIV disclosure intervention to address the diverse needs of HIV-infected people.